The constitutional control of legislative acts as progress and future of constitutionalism - Cea Egaña, José Luis (Revista de Derecho Público, 2015)
The 20th century was, in Chile and the world, a time of great changes in Constitutional Law, although constitutionalism, which is not the same thing, kept its humanistic essence and limited government unchanged. Consequently, there was a mismatch between the principles with which the Fundamental Charter should be understood and implemented, on the one hand, and the articulation of those principles in its positive text, on the other.